Labouring Canada: Class, Gender, and Race in Canadian Working-Class History - Palmer, Bryan D.; Sangster, Joan (Oxford University Press, 2008)
This text is a collection of classic and contemporary articles exploring the nature of work in Canadian history from the late eighteenth century to the current day. Class relations and labour form the core of the volume, but attention will also be paid to the state and its relations with workers both formal and informal. The volume is designed as a core text for classes in Canadian labour/working-class history, taught out of history and labour studies departments. --Publisher's description
Keywords: Canada; History; Labor movement; Social history; Working class